Analysis of ethos, pathos and logos in leadership communication through the work of faisal tehranis nama Beta Sultan Alaudin [Analisis ethos, pathos dan logos dalam komunikasi kepimpinan nama Beta Sultan Alauddin Karya Faisal Tehrani] - Nordiana Hamzah (Tanjung Malim, 2023)
Analysis of ethos, pathos and logos in leadership communication through the work of faisal tehranis nama Beta Sultan Alaudin [Analisis ethos, pathos dan logos dalam komunikasi kepimpinan nama Beta Sultan Alauddin Karya Faisal Tehrani] by Nordiana Hamzah